2022
DOI: 10.1177/10738584221130974
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Brain Activity from Connectivity: Advances and Applications

Abstract: The human brain is composed of multiple, discrete, functionally specialized regions that are interconnected to form large-scale distributed networks. Using advanced brain-imaging methods and machine-learning analytical approaches, recent studies have demonstrated that regional brain activity during the performance of various cognitive tasks can be accurately predicted from patterns of task-independent brain connectivity. In this review article, we first present evidence for the predictability of brain activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…This is consistent with previous findings that task activation maps predicted by resting-state fMRI better predict cognitive variables such as intelligence than real task activation maps (Gal, Coldham, et al, 2022; Gal, Tik, et al, 2022). This advancement suggests that resting-state fMRI-derived task activation maps, particularly those generated by SwiFUN, hold significant potential to reflect cognitive and biological traits more accurately than traditional task activation maps, which may be under the influence of nuisance variables (head motion, scanning artifacts, attention level fluctuations) (Bernstein-Eliav & Tavor, 2022). Such capability implies broader applications for SwiFUN, including the potential for diagnosing and predicting psychiatric disorders, thereby positioning it as a valuable tool in neuroscientific research and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous findings that task activation maps predicted by resting-state fMRI better predict cognitive variables such as intelligence than real task activation maps (Gal, Coldham, et al, 2022; Gal, Tik, et al, 2022). This advancement suggests that resting-state fMRI-derived task activation maps, particularly those generated by SwiFUN, hold significant potential to reflect cognitive and biological traits more accurately than traditional task activation maps, which may be under the influence of nuisance variables (head motion, scanning artifacts, attention level fluctuations) (Bernstein-Eliav & Tavor, 2022). Such capability implies broader applications for SwiFUN, including the potential for diagnosing and predicting psychiatric disorders, thereby positioning it as a valuable tool in neuroscientific research and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to issues such as ensuring participant compliance and motivation, as well as the necessity for strict experimental control. These issues become particularly pronounced in specific groups such as children, the elderly, and individuals with neurocognitive disorders or severe psychiatric conditions (Bernstein-Eliav & Tavor, 2022; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these structural connectivity predictions, previous research has demonstrated a close link between functional connectivity and task activity 25 . Note that while structural and functional connectivity are correlated, the link between these two measures remains unclear 26 .…”
Section: Introductionmentioning
confidence: 86%
“…Over the last decade, there has been growing interest and important developments for characterization of the brain connectome to obtain useful and meaningful information while exploring a wide range of pathological conditions and cognitive mechanisms (Bijsterbosch et al, 2021 ; Bernstein-Eliav and Tavor, 2022 ; Srivastava et al, 2022 ). The brain connectome can be investigated using various connectivity measures such as structural (anatomical) and functional (neuronal) connectivity within and between regions in the brain (Babaeeghazvini et al, 2021 ).…”
mentioning
confidence: 99%